Geographic Markets, Causality and Railroad Deregulation - Uri, Noel D.; Rifkin, Edward J. (The Review of Economics and Statistics, 1985)
This paper presents an approach to defining a market using the notion of instantaneous causality. The market for which the approach is empirically implemented is the flour market in the United States over the period January 1979 through October 1982. One anomaly over this period was the deregulation of railroad rates in October 1980. The empirical results based on three spatially diffuse cities suggest that the market is national in scope and that after railroad deregulation the price interrelationship between cities was strengthened.